IBS defects before completion of project at Kem 4 Rejimen Renjer Diraja (4RRD) Oran, Perlis / Nur Syamira Sapri - Sapri, Nur Syamira (Universiti Teknologi Mara, Perak, 2016)
Usima Sdn. Bhd. is a company G7 class construction contractor based in Light Industry Park, Sri Phase, 05150 Alor Setar, Kedah. The company is owned by Dato 'Hj. Mohd Yusof b. Hj. Ismail, the managing director for Usima Sdn. Bhd. since 1990. Services provided by this company are mechanical work, construction work, road work, electrical work and the work of other relevant construction contract. For over 20 years, Usima Sdn. Bhd. has built a reputation as one of the most forward thinking construction companies in Malaysia. The company has won numerous achievements recognized by CIDB, SME Corp and also from Perkeso. Usima Sdn. Bhd. was incorporated on 23th October 1990. With a focus on its strengths in building construction and public works, Usima Sdn. Bhd. has grown and established itself as a credible performance contractor in construction of buildings and civil works. With the board members and staff who are dedicated and committed, Usima Sdn. Bhd. then secured recognition from the CIDB on 19th September 1996 as a contractor grade G7. This became the catalyst for the company to strive harder to achieve success and even greater goals.